A simulation of the effects of breeding season on the productivity of Small East African goats on a Kenyan rangeland - Carles, A.B.; Blackburn, H.D.; Schwartz, H.J. (1992)
Seasonal breeding is potentially a powerful intervention affecting productivily, particularly so in semi-arid environments where seasonal differences are great; however, variability is also great, increasing the risk for such interventions. Simulation was used to examine the effects of 5 breeding regimes covering the range of the main possibilities. For breeding once a year, these were (l) mating and birth at times of favourable forage: (2) mating at; and (3) mating at a favourable and birth at an unfavourable time. For more frequent breeding, simulations were for (4) mating 3 times in 2 years; and (5) mating for 10 months of the year (all other systems were confined to 2 months). The rankings for productivity and efficiency were the same for all 5 breeding regimes. The first system had the highest absolute level of production and efficiency; on a biomass basis; this system was 226% higher than the least (3), and 22% higher than the regime considered to have the least risk (5). On energy basis efficiencies ranged from 10.5 to 5.9%. Milk production was the highest, and risk was the lowest for the last two. So the final choice should depend on qualitative aspects of the different products, and the acceptable level of risk, as well as the absolute level and efficiency of production.